2010
DOI: 10.1007/s00467-010-1672-1
|View full text |Cite
|
Sign up to set email alerts
|

Residual renal function assessment with cystatin C

Abstract: Su Jin Kim and coworkers from Korea published an important study on the relationship of residual renal function (RRF) and cystatin in pediatric peritoneal dialysis (PD) patients in this issue of Pediatric Nephrology, both in anuric patients and patients with RRF. Based on a lack of correlation between cystatin C and standard small solutebased dialysis adequacy parameters such as Kt/V urea but a significant correlation with RRF, the authors concluded that cystatin C may be a good tool to monitor RRF. The editor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…This study showed that cystatin C measured before the dialysis was significantly correlated with mean creatinine (r = 0.505; P < 0.001) (13). Consistent with our findings, Guido Filler introduced cystatin C as a useful marker for monitoring children under dialysis (14). Similarly, correlation between cystatin C and Kt/V (sp) in patients on conventional or nocturnal hemodialysis was not found in other studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study showed that cystatin C measured before the dialysis was significantly correlated with mean creatinine (r = 0.505; P < 0.001) (13). Consistent with our findings, Guido Filler introduced cystatin C as a useful marker for monitoring children under dialysis (14). Similarly, correlation between cystatin C and Kt/V (sp) in patients on conventional or nocturnal hemodialysis was not found in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, correlation between cystatin C and Kt/V (sp) in patients on conventional or nocturnal hemodialysis was not found in other studies. However, they could show its correlation with standard weakly Kt/V (12, 14, 15), which may support the promising role of serum cystatin C level as a rough estimator of dialysis adequacy and residual renal function.…”
Section: Discussionmentioning
confidence: 75%
“…Given the cumbersome nature of the urine collections, there has been increasing interest in filtration markers obtainable through a single blood draw that can obviate the need for urine collection. In PD patients, serum cystatin C is correlated with RKF (r 2 ;0.7), and a number of recent studies have explored its use for estimation of RKF (28)(29)(30)(31). Cystatin C, a 13.2-kD protein, is about the same size as b-2 microglobulin (11.8 kD) and is removed effectively by high-flux hemodialysis, limiting its use as a serum marker of RKF in hemodialysis patients (17,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Cystatin C has not been shown to be superior to calculation of GFR through the Schwartz formula in neonates [ 198 ]. Data on cystatin C in children receiving RRT are scarce [ 199 202 ].…”
Section: Kidney Function and Its Impact On Drugs In Pediatric Patientmentioning
confidence: 99%